Efektivitas Penggunaan Qris Terhadap Persepsi dan Keputusan Pembelian Konsumen pada Pedagang Kaki Lima di Simpang Tujuh Kudus - Naili Fauziyatul Husna; Avira Budianita; Fifi Endah Irawati (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2025)
The development of financial technology in Indonesia has introduced a digital payment innovation known as Quick Response Code Indonesian Standard (QRIS), launched by Bank Indonesia in 2019 to unify various QR-based payment services into a more practical, fast, and secure system. QRIS implementation is not limited to the formal sector but has also reached street vendors (PKL), including those in Simpang Tujuh Kudus, one of the main trade centers. However, its utilization remains suboptimal as many vendors have not consistently activated, displayed, or offered QRIS to customers. This condition raises the question of how consumer perception is formed toward QRIS and whether it influences purchasing decisions. This study aims to analyze the effectiveness of QRIS usage on consumer perception and its impact on purchasing decisions. A quantitative method was applied using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software, and data were collected through questionnaires with a Likert scale. The results indicate that QRIS usage has a positive and significant effect on consumer perception; consumer perception significantly affects purchasing decisions and acts as a mediating variable between QRIS usage and purchasing decisions. Thus, optimal utilization of QRIS strengthens consumer trust and positive perception, while simultaneously encouraging purchasing decisions among street vendors in Simpang Tujuh Kudus.